Development of English Learning Media Using Adobe Animate in the Material Pronoun - Cindy Aprilia Sarno; Pahmi Pahmi; Ardiya Ardiya (Universitas Lancang Kuning, 2022)
To interact with others around the world and to learn a foreign language, English is used. In Indonesia, English is taught as a foreign language in schools. So, teachers need a media to teach English. Media and software platforms like Adobe Animate (formerly known as Macromedia Flash and Shockwave Flash) enable the creation of various types of multimedia content including vector graphics and animation. The purpose of research is to know the development of English learning media using adobe animate in the material of pronoun at seventh grade students of junior high school. The research method used Research and Development or commonly known as R&D. This research was tested on the seventh grade students’ as population at MTs Muhammadiyah 02 Pekanbaru. The sample was taken from a class in the seventh grade which total of 36 people. The research was carried out in June 2022, at the MTs Muhammadiyah 02 Pekanbaru. Based on the research result, it can be concluded that the learning media developed has successfully undergone alpha and beta testing to determine its feasibility. It can affirm that the application of English learning media in the material Pronoun using adobe animate android-based software is suitable for use by students in learning. The average pretest result of was 6,2. Then the average post-test result was 7,9. Based on Figure 4, it can be seen that the gain score is 0,70. The value is based on the classification of the gain value is in the high classification.